Salt mill complex and warehouses of the former salt mine in Wapno. Considerations and premises for the protection of 20th-century post-industrial buildings as a permanent ruin - Urbaniak, Miron (Protection of Cultural Heritage, 2018)
In the former salt mine, destroyed by water in 1977, a salt mill complex together with salt warehouses can be seen from a distance in the small village of Wapno in Wielkopolska. Designed under the guidance of prof. Bronisław Bukowski (1893–1965), and erected in 1929–1930 by C. Lubiński and K. Jaskulski from Warsaw, the buildings have a reinforced concrete frame system and a supporting column support structure. The complete setup is characterized by a huge scale, disproportionate to the current needs of a small village, which hinders any possibility of revitalization and adaptation to new functions. However, the value of the buildings for the history and the Wapno panorama, which was once home to the largest salt mine in Poland, for the cultural landscape of Wielkopolska, and finally for the history of Polish salt mining and the Polish school of concrete and reinforced concrete construction, is difficult to be estimated. That is why regardless of the deteriorating condition, the complex should definitely be protected and preserved in the cultural landscape of Wielkopolska as a highly valuable technical monument. At the same time at this point the only way to protect it is to preserve it as a permanent ruin.